Pengaruh Variasi Kecepatan Putar Dan Waktu Gesek Terhadap Kekuatan Impak Sambungan Las Gesek Pada Baja AISI 4340 - Saputra, Maula; Rodika, Rodika; Ary Wahyudie, Ilham (Politeknik Manufaktur Negeri Bangka Belitung, 2023)
Welding is a very important process in the industrial world and is not left behind in today's developments. Friction welding techniques that rely on heat by friction of two materials, besides this friction welding without the use of filler metal or electrodes and the processing time is not long, this friction welding is very good for solid objects such as shafts. At this time, a test will be carried out on the effect of variations in rotational speed and friction time on the impact strength of joints in AISI 4340 steel. This study will use lathes with variations in rotational speed parameters of 720, 1000 and 1400 rpm with times of 50, 70 and 90 seconds. The material used is AISI 4340 steel in the form of a solid cylinder and impact strength testing will be carried out using the charpy method. From the research conducted, the highest average results were obtained, namely at 1400 Rpm and with a time of 90 seconds with an impact energy value of 31.93 J and an average impact price of 0.398 J/mm2. While the lowest average value is at 720 rpm variation and with a time of 50 seconds with an impact energy value of 6.43 J and an average impact price of 0.079 J/mm2. So variations in the parameters of rotational speed and friction time greatly affect the strength of the material to be impact tested.